Metal-organic vapor-phase epitaxial growth of InGaN and InAlN for multi-junction tandem solar cells - Yamamoto, A.; Sugita, K.; Bhuiyan, A. G.; Hashimoto, A.; Narita, N. (Materials for renewable and sustainable energy, 2013)
Metal-organic vapor-phase epitaxial (MOVPE) growth of InGaN and InAlN has been studied to prepare a wanted band-gap from 0.65 to 2.5 eV for multi-junction tandem solar cells. The main subjects in the growth of InGaN are the suppression of phase separation and metallic In incorporation and the control of composition in grown films. Both phase separation and metallic In segregation can be avoided by choosing the appropriate substrate position on the susceptor. By optimizing growth temperature and TMI/(TMI + TEG) molar ratio, InGaN films with full composition range are successfully grown. The Mg-doping behavior of MOVPE InGaN (In composition 0.1–0.4) is also studied using Cp 2 Mg as a Mg source. The growth behavior of InAlN is studied with the dominant parameters such as growth pressure, TMI/(TMI + TMA) molar ratio and substrate position on the susceptor. The major difficulty in the InAlN growth is found to be the adduct formation by the parasitic reaction of TMA and NH 3 . By employing the atmospheric-pressure growth, adduct-free InAlN films are grown with a reasonable growth rate (~1 μm/h). This enables us to grow InAlN films with an In content from 0.3 to 1, corresponding to band-gaps from 3.6 to 0.65 eV. In order to demonstrate an ability to prepare these different alloys sequentially, InAlN/InGaN hetero-structures are prepared and the photo-response is observed for the first time for an n-InAlN/p-InGaN hetero-junction.